Road safety audit ‐ possibility to avoid a dangerous road section - Pikūnas, Alvydas; Pumputis, Vidmantas (Transport, 2005)
The number of road traffic casualties is still very high, even though the number of fatalities in European countries is falling. In road traffic accidents involving personal injury, economic resources are destroyed and the productivity of economy is correspondingly impaired. Costs resulting from traffic accidents represent the largest single part of the overall cost of traffic in economus. Knowledge about the harm it does to economy is essential if measures to reduce road traffic accidents are identified and introduced. Economic evaluation of road safety measures using cost‐benefit analysis is based on the costs incurred as a result of road accidents. The avoidance of such costs represents the economic benefit of road safety measures. Road safety audit is a formal procedure for independent assessment of the accident potential and likely safety performance of a specific design for a road or traffic scheme ‐ either new construction or alteration of an existing road.First Published Online: 27 Oct 2010